Cross-link augmentation enhances CFR-PEEK short fixation in lumbar metastasis stabilization - Borrelli, Simone; Putame, Giovanni; Audenino, Alberto L.; Bignardi, Cristina; Ferro, Andrea; Marone, Stefano; Terzini, Mara (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Spinal stability plays a crucial role in the success of the surgical treatment of lumbar vertebral metastasis and, in current practice, less invasive approaches such as short constructs have been considered. Concurrently, carbon fiber-reinforced (CFR) poly-ether-ether-ketone (PEEK) fixation devices are expanding in oncologic spinal surgery thanks to their radiotransparency and valid mechanical properties. This study attempts to provide an exhaustive biomechanical comparison of different CFR-PEEK surgical stabilizations through a highly reproducible experimental setup. Methods: A Sawbones biomimetic phantom (T12-S1) was tested in flexion, extension, lateral bending, and axial rotation. An hemisome lesion on L3 vertebral body was mimicked and different pedicle screw posterior fixations were realized with implants from CarboFix Orthopedics Ltd: a long construct involving two spinal levels above and below the lesion, and a short construct involving only the levels adjacent to L3, with and without the addition of a transverse rod-rod cross-link; to provide additional insights on its long-term applicability, the event of a pedicle screw loosening was also accounted. Results: Short construct reduced the overloading onset caused by long stabilization. Particularly, the segmental motion contribution less deviated from the physiologic pattern and also the long-chain stiffness was reduced with respect to the prevalent long construct. The use of the cross-link enhanced the short stabilization by making it significantly stiffer in lateral bending and axial rotation, and by limiting mobiliza-tion in case of pedicle screw loosening. Discussion: The present study proved in vitro the biomechanical benefits of cross-link augmentation in short CFR-PEEK fixation, demonstrating it to be a potential alternative to standard long fixation in the surgical management of lumbar metastasis.